Unraveling Exhaustion in Adaptive and Conventional Natural Killer Cells - Merino, Aimee M (J Leukoc Biol, 2020)
Immune exhaustion in T cells significantly impacts their ability to control malignancies and infections, and its discovery has led to revolutionary therapies for cancer in the form of checkpoint blockade. Natural killer (NK) cells, like T cells, are lymphocytes that recognize virally infected and malignantly transformed cells. However, it remains unclear if NK cells are similarly susceptible to exhaustion. In this review we seek to summarize what is currently known and to identify key areas of variability that skew the scientific literature on NK cell exhaustion. A lack of consensus on the defining features of NK cell dysfunctional states such as senescence, suppression, and exhaustion has made comparison between studies difficult. There are also significant differences in the biology of NK cell subsets with long-lived, adaptive NK cells sharing an epigenetic signature closer to memory CD8(+) T cells than to conventional NK cells. We have shown very different checkpoint receptor expression and effector functions in adaptive versus conventional NK cells chronically exposed to activating signals. Adaptive NK cells develop in individuals with cytomegalovirus (CMV) infection and well over half of the human population worldwide is CMV seropositive by adulthood. Despite this high prevalence, most studies do not account or control for this population. This may contribute to some of the variability reported in the literature on checkpoint receptor expression on NK cells. In this review we will also discuss the protective role that exhaustion plays in T cells and examine evidence for a similar phenomenon in NK cells.